2023
DOI: 10.3390/nu15122698
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet Controls Offspring Kidney Health and Disease

Abstract: A balanced diet during gestation is critical for fetal development, and excessive intake of saturated fats during gestation and lactation is related to an increased risk of offspring kidney disease. Emerging evidence indicates that a maternal high-fat diet influences kidney health and disease of the offspring via so-called renal programming. This review summarizes preclinical research documenting the connection between a maternal high-fat diet during gestation and lactation and offspring kidney disease, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 179 publications
(296 reference statements)
0
1
0
Order By: Relevance
“…It is known that the maternal nutrition and intrauterine environment play a key role in the development of metabolic disease in offspring ( 5 ). Recent studies on the underlying mechanisms of this programming effect have found that maternal diets can affect insulin and glucose metabolism, energy balance, cardiovascular function, and obesity in offspring ( 6 , 7 ). In addition, there is evidence that changes in epigenetic marks are one mechanism that could account for such long-term effects, as they affect gene expression and thus shape the phenotype of the organism ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the maternal nutrition and intrauterine environment play a key role in the development of metabolic disease in offspring ( 5 ). Recent studies on the underlying mechanisms of this programming effect have found that maternal diets can affect insulin and glucose metabolism, energy balance, cardiovascular function, and obesity in offspring ( 6 , 7 ). In addition, there is evidence that changes in epigenetic marks are one mechanism that could account for such long-term effects, as they affect gene expression and thus shape the phenotype of the organism ( 8 ).…”
Section: Introductionmentioning
confidence: 99%